Physiological changes in cycle rickshaw pullers after strenuous exercise - Debashis Manna; Sridhar Thakur; Chandan K Pradhan (Occupational Health and Safety Society of Nepal, 2012)
Background: Cycle Rickshaw is a human-powered transportation device. A large number of people remain engaged in the occupation of pulling cycle rickshaw. Objectives: The objectives of the study were to assess nutritional status of the cycle rickshaw pullers and their workload by working heart rate and energy expenditure. Methods and Materials: Eighteen rickshaw pullers and eleven control subjects were selected after clinical examination. Subjects were asked to pull the rickshaw in two phases - phase 1 (before lunch) and phase 2 (after lunch) each of 3 cycles of 15 min duration each followed by 15 min rest with two passengers. Heart rate was recorded continuously using a heart rate monitor. Average working heart rate (AWHR), peak working heart rate (PWHR) and energy expenditure (EE) were calculated. Maximal heart rate (HRmax) was also recorded in the laboratory. The control subjects were allowed to work in a cycle ergometer in the laboratory. Results: There was no significant difference between the mean values of rickshaw pullers and those of control subjects in relation to age, BMI, fat% and HRmax (beats/min). The AWHR, PWHR and EE values of rickshaw pullers showed the workload as 'heavy' to 'very heavy' category. Conclusion: The result of the study will be beneficial for cycle rickshaw pullers, health administrators and manufacturers of cycle rickshaw. DOI: http://dx.doi.org/10.3126/ijosh.v2i2.6567 International Journal of Occupational Safety and Health, Vol 2. No 2 (2012) 23-26